Barriers in the Decision Making About and Performance of Continuous Sedation Until Death in Nursing Homes. (18th December 2019) - Robijn, Lenzo; Deliens, Luc; Rietjens, Judith; Pype, Peter; Chambaere, Kenneth
Abstract: Background and Objectives: While decision making about and performance of continuous sedation involve many challenges, they appear to be particularly pervasive in nursing homes. This study aims to identify barriers to the decision making and performance of continuous sedation until death in Flemish nursing homes as experienced by the health care professionals involved. Research Design and Methods: Ten focus groups were held with 71 health care professionals including 16 palliative care physicians, 42 general practitioners, and 13 nursing home staff. Discussions were transcribed verbatim and analyzed using a constant comparative approach. Results: Perceived barriers concerned factors prior to and during sedation and were classified according to three types: (a) personal barriers related to knowledge and skills including the lack of clarity on what continuous sedation should be used for (linguistic ambiguity) and when and how it should be used (practical ambiguity); (b) relational barriers concerning communication and collaboration both between health care professionals and with family; (c) organizational barriers related to the organization of care in nursing homes where, for example, there is no on-site physician, or where the recommended medication is not always available. Discussion and Implications: The findings suggest there are considerable challenges for sound decision making about and performance of continuous sedation until death in nursing homes. There is a need for multicomponent initiatives that provide guidance in the context of the complexity of a resident's medical situation, the family, and the specific organization of care, which would have the potential to facilitate and improve the decision-making process and performance of continuous sedation in nursing homes.